Preparation method and application of modified ZnO nanoparticles

By synthesizing ZnO nanoparticles with DNA as template and treated with H2O2, the problem of ZnO nanoparticles burst release in the wound environment was solved, and the balance between antibacterial activity and biosafety was achieved, and modified ZnO nanoparticles were formed for wound coagulation. Glue agent significantly improves antibacterial effect and wound healing ability.

CN119191337APending Publication Date: 2024-12-27CENT SOUTH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311163.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

ZnO nanoparticles are prone to cause large-scale sudden release of Zn2+ in wound environments, damaging skin cells, and it is difficult to achieve a balance between antibacterial activity and biosafety.

Method used

ZnO nanoparticles were synthesized using DNA as a template, and treated with H2O2 significantly improved the antibacterial activity and biosafety of ZnO nanoparticles, and formed modified ZnO nanoparticles, which were used to make external gel agents to antibacterial and promote wound healing.

Benefits of technology

The antibacterial activity of modified ZnO nanoparticles is enhanced, the Zn2+ release rate slows down, and the biosafety is improved. Gel agents not only have antibacterial effects on wounds, but also promote wound healing and reduce inflammation and scar production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191337A_ABST
    Figure CN119191337A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of modified ZnO nanoparticles, ZnO nanoparticles are prepared by using Zn salt as a raw material and DNA as a template, and then the modified ZnO nanoparticles are obtained by treatment with an H2O2 solution. The modified ZnO nanoparticles have higher stability, photocatalytic activity, antibacterial activity and biological safety, and an external preparation prepared from the modified ZnO nanoparticles as a raw material can play a bactericidal role when applied to a wound surface, and also can promote wound healing and reduce inflammation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano materials, and in particular to a preparation method and application of modified ZnO nanoparticles. Background Art

[0002] ZnO is an inorganic material with antibacterial effect. It can directly contact with bacteria and destroy the cell wall of bacteria, causing the loss of bacterial contents and killing bacteria. In addition, ZnO can also produce reactive oxygen species (ROS) under the action of photocatalysis to kill bacteria. 2+ It can also interfere with the normal physiological activities of bacteria, including protein translation, energy metabolism, and biofilm formation, thereby inducing bacterial death. Applying ZnO nanoparticles to medical dressings can provide antibacterial protection for wounds, reduce wound infection, and promote wound healing. However, since the wound is in a special environment, ZnO nanoparticles are prone to Zn 2+ A large amount of sudden release can damage skin cells and cause toxic side effects to the wound site. Therefore, in order to improve the antibacterial activity and biosafety of ZnO nanoparticles, they need to be modified.

[0003] The literature Liu, Suiping et al. "The influence of H2O2 on the antibacterial activity of ZnO." Materials Research Express 6 (2019): n.pag. discloses a method for modifying ZnO nanoparticles using H2O2. ZnO nanoparticles are synthesized using Zn(NO3)2·6H2O as a raw material, and then sealed with 30% H2O2 and heated in a water bath overnight to complete the modification of the ZnO nanoparticles. The modified ZnO nanoparticles Zn 2+ The release is slowed down, but at the same time its antibacterial activity is also weakened, making it difficult to achieve a balance between antibacterial activity and biosafety. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a preparation method and application of modified ZnO nanoparticles. ZnO nanoparticles are synthesized using DNA as a template and then modified using H2O2, which can significantly improve the antibacterial activity and biosafety of the ZnO nanoparticles. The external gel prepared using the modified ZnO nanoparticles as raw materials can be used for wound antibacterial, and can also promote wound healing and reduce inflammation.

[0005] The technical solution of the present invention is:

[0006] A method for preparing modified ZnO nanoparticles comprises the following steps: using Zn salt as a raw material and DNA as a template to prepare ZnO nanoparticles, and then treating the ZnO nanoparticles with a H2O2 solution to obtain the modified ZnO nanoparticles.

[0007] DNA can be used as a biological template for the synthesis of ZnO nanomaterials due to its biocompatibility and editability. H2O2 is a chemical etching agent. After ZnO nanoparticles are treated with H2O2, their structural composition and size do not change significantly, but their interface properties will change significantly, including stability, photocatalytic activity and adhesion, thereby changing the antibacterial activity and cytotoxicity of ZnO nanoparticles.

[0008] As a further preferred embodiment of the above scheme, the preparation method comprises the following steps: mixing the Zn salt raw material and the DNA template and heating them, adjusting the pH to alkaline, and then adding H2O2 solution and heating them to obtain modified ZnO nanoparticles.

[0009] The Zn salt of the present invention is the Zn source of ZnO nanoparticles, and can be various inorganic Zn salts and organic Zn salts, such as ZnCl2, ZnSO4, Zn(OAc)2, Zn(NO3)2, ZnCO3, Zn3(PO4)2, ZnBr2, Zn(C6H 11 O7)2 (zinc gluconate), etc. The synthesis of ZnO nanoparticles in the present invention is preferably carried out in water, so the Zn salt raw material is preferably a water-soluble Zn salt, such as Zn(OAc)2, Zn(NO3)2, ZnSO4, etc.

[0010] As a further preferred embodiment of the above scheme, the concentration of the DNA template is 0.0001-100 μM, preferably 1-10 μM. It is understood that this concentration is the final concentration of the DNA template in the system, not the reagent concentration.

[0011] DNA is used as a template for synthesizing nanoparticles. Its phosphate backbone also plays a certain stabilizing role. Single-stranded DNA, such as poly-C DNA, double-stranded DNA, such as A / T double-stranded DNA, or free nucleotides, such as free cytosine, can be used. Among them, ZnO nanoparticles synthesized using single-stranded DNA as a template have a more regular morphology, a small particle size, and high uniformity.

[0012] As a further preferred embodiment of the above scheme, the single-stranded DNA template can be one of poly-A, poly-G, poly-T, and poly-C DNA, or a mixture of two or more of the single-stranded DNAs.

[0013] The poly-A DNA referred to in the present invention is a polyadenine nucleotide, the poly-T DNA is a polythymine nucleotide, the poly-C DNA is a polycytosine nucleotide, and the poly-G DNA is a polyguanine nucleotide.

[0014] As a further preferred embodiment of the above scheme, the single-stranded DNA is poly-C DNA.

[0015] As a further preferred embodiment of the above scheme, the base sequence length of the DNA is 1-40 bases, preferably 20 bases.

[0016] It is understandable that during the synthesis of ZnO nanoparticles, the system needs to be controlled to be alkaline. After adding the Zn salt raw material and the DNA template, it is usually necessary to add an additional alkaline regulator, which can be an inorganic base such as NaOH or an organic base such as DEA (diethanolamine).

[0017] As a further preferred embodiment of the above scheme, the preparation method of the modified ZnO nanoparticles comprises the following steps: mixing Zn(OAc)2·2H2O and poly-C DNA with a base sequence length of 20 bases in water and then heating, adjusting the pH to alkaline to obtain a reaction solution containing ZnO nanoparticles, adding a 30% H2O2 solution to the reaction solution, mixing and heating, filtering and washing, and obtaining modified ZnO nanoparticles.

[0018] An application of the modified ZnO nanoparticles obtained based on any one of the above preparation methods, comprising preparing an external preparation using the modified ZnO nanoparticles as a raw material.

[0019] As a further preferred embodiment of the above scheme, the external preparation is a gel.

[0020] As a further preferred embodiment of the above scheme, the external preparation is used for antibacterial treatment of wound surfaces.

[0021] As a further preferred embodiment of the above scheme, the external preparation is used to promote wound healing, especially to promote the healing of infected wounds.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) ZnO nanoparticles synthesized using DNA as a template have a uniform spindle-shaped structure and a smaller particle size and higher uniformity than ZnO nanoparticles synthesized without using DNA as a template;

[0024] (2) The modified ZnO nanoparticles obtained by treating ZnO nanoparticles with H2O2 had no significant changes in their structural composition and size, but their surface roughness increased significantly, and their colloidal stability, acid stability and photocatalytic activity were significantly improved, and their antibacterial activity was enhanced. At the same time, the modified ZnO nanoparticles had specific adhesion to bacteria. 2+ The release rate is also slowed down, the toxicity to cells is reduced, and the biosafety is improved;

[0025] (3) The gel made from modified ZnO nanoparticles not only has an antibacterial effect on the wound surface, but also can promote wound healing and reduce inflammation and scar formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 TEM images of ZnO-1 to ZnO-10;

[0028] Figure 2 TEM images of ZnO-1 and H-ZnO-1;

[0029] Figure 3 DLS particle size distribution diagram of ZnO-1 and H-ZnO-1;

[0030] Figure 4 Surface zeta charge diagrams of ZnO-1 and H-ZnO-1;

[0031] Figure 5 It is the UV-visible absorption spectra of ZnO-1, H-ZnO-1 and reagents;

[0032] Figure 6 The infrared absorption spectra of ZnO-1 and H-ZnO-1;

[0033] Figure 7 Raman spectra of ZnO-1 and H-ZnO-1;

[0034] Figure 8 The actual pictures of ZnO-1 and H-ZnO-1 before and after being placed at room temperature for 24 hours;

[0035] Fig. 9 ZnO-1 and H-ZnO-1 in different pH buffer solutions 2+ Release kinetics diagram;

[0036] Fig.10 TEM images of ZnO-1 and H-ZnO-1 after incubation in pH 5.5 buffer for 5 min and 30 min;

[0037] Fig.11 Photocatalytic production of ·OH and ·O2 by ZnO-1 and H-ZnO-1 - ESR test result diagram;

[0038] Fig.12 Photocatalytic production of ·OH and ·O2 by H-ZnO-1 at different concentrations - ESR test result diagram;

[0039] Fig.13 This is a graph showing the antibacterial effect of different concentrations of ZnO-1 under different lighting conditions;

[0040] Fig.14 The antibacterial effect diagram of different concentrations of H-ZnO-1 under different lighting conditions;

[0041] Fig.15 TEM images of the microscopic morphology of bacteria treated with ZnO-11 and H-ZnO-11;

[0042] Fig.16 is the intracellular ROS fluorescence level of bacteria after ZnO-1 and H-ZnO-1 were treated in dark;

[0043] Fig.17 The cytotoxicity results of ZnO-1 and H-ZnO-1 on L929 cells;

[0044] Fig.18 The adhesion of ZnO-1 and H-ZnO-1 to cells;

[0045] Fig.19 The stimulation of ZnO-1 and H-ZnO-1 on blood vessels;

[0046] Fig. 20 The wound photos of mice in each group at different times in Test Example 11;

[0047] Fig.21 The relative wound area changes of each group of mice in Test Example 11;

[0048] Fig. 22 The results of wound tissue fluid plating of each group of mice at different times in Test Example 11;

[0049] Fig.23 The H&E staining results of the skin tissue of each group of mice in Test Example 11 after 13 days of treatment;

[0050] Fig.24The expression levels of TNF-α, IL-1β, IL-6 and IL-10 in the skin of each group of mice in Test Example 11 after 9 days of treatment;

[0051] Fig.25 The immunofluorescence imaging results of α-SMA and CD31 in the skin of each group of mice in Test Example 11;

[0052] Fig.26 The Masson staining results of the skin tissue of each group of mice in Test Example 11;

[0053] Fig. 27 The wound photos of mice in each group at different times in Test Example 12;

[0054] Fig.28 The relative wound area changes of each group of mice in Test Example 12;

[0055] Fig.29 The expression levels of TNF-α, IL-1β, IL-6 and IL-10 in the skin of each group of mice in Test Example 12 after 9 days of treatment;

[0056] Fig.30 The immunofluorescence imaging results of α-SMA and CD31 in the skin of each group of mice in Test Example 12;

[0057] Fig.31 The Masson staining results of the skin tissues of mice in each group in Test Example 12;

[0058] Fig.32 The expression level of TGF-β in the wound tissue of each group of mice in Test Example 12. DETAILED DESCRIPTION

[0059] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0060] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0061] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0062] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0063] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0064] Zinc acetate dihydrate, sodium hydroxide, and glacial acetic acid were purchased from Sinopharm Chemical Reagent Co., Ltd., reactive oxygen species detection kit was purchased from Shanghai Bio-Tech Biotechnology Co., Ltd., N-acetylcysteine ​​was purchased from Shanghai Yuanye Biotechnology Co., Ltd., 3,3',5,5'-tetramethylbenzidine (TMB) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., DNA was purchased from Qingke Biotechnology Co., Ltd., intracellular zinc ion probe (TSQ) was purchased from MedChemExpress Co., Ltd., heavy metal chelator (TPEN) was purchased from Shanghai Maokang Biotechnology Co., Ltd., and phalloidin cytoskeleton probe, LB broth, and LB broth agar were purchased from Beijing Solebao Technology Co., Ltd. All reagents were not further purified. All reagents were prepared with double distilled water.

[0065] Example 1

[0066] Using poly-C DNA with a base sequence length of 20 (denoted as C20, the same below) as a template, 500 μL of 10 mM Zn(OAc)2·2H2O solution and 50 μL of 100 μM C20 were added to 250 μL ultrapure water in sequence, vortexed to mix, placed in a hot water bath at 85°C, 200 μL of 100 mM NaOH solution was added thereto to adjust the pH to alkaline, ultrasonicated for 30 min, and incubated at room temperature for 2 h to obtain a first reaction solution. The first reaction solution was centrifuged at 20,000 rpm for 20 min, the supernatant was discarded, and the solution was washed twice with ultrapure water to obtain ZnO nanoparticles, denoted as ZnO-1.

[0067] The first reaction solution was mixed with 30% H2O2 solution in equal volumes, and treated in a hot water bath at 85°C for 0.5 h to obtain a second reaction solution. The second reaction solution was centrifuged at 20,000 rpm for 20 min, the supernatant was discarded, and the solution was washed twice with ultrapure water to obtain modified ZnO nanoparticles, recorded as H-ZnO-1.

[0068] Example 2

[0069] Using C20 as a template, 500 μL of 10 mM Zn(NO3)2·6H2O solution and 50 μL of 100 μM C20 were added to 250 μL ultrapure water in sequence, vortexed to mix, placed in a 60°C hot water bath, and 100 mM NaOH solution was added to adjust the pH of the reaction system to about 9. After ultrasonication for 10 min, the mixture was incubated at room temperature for 3 h to obtain a first reaction solution. The first reaction solution was centrifuged at 20,000 rpm for 20 min, the supernatant was discarded, the mixture was washed twice with ultrapure water, and dried to obtain ZnO nanoparticle powder, recorded as ZnO-2.

[0070] The ZnO nanoparticle powder was completely immersed in a 30% H2O2 solution, treated in a 70°C hot water bath for 20 minutes, centrifuged at 20,000 rpm for 20 minutes, and the supernatant was discarded. The powder was washed twice with ultrapure water to obtain modified ZnO nanoparticles, which were recorded as H-ZnO-2.

[0071] Example 3

[0072] The C20 template was replaced with a poly-A DNA having a base sequence length of 20, denoted as A20, and ZnO-3 and H-ZnO-3 were obtained according to the preparation method of Example 1.

[0073] Example 4

[0074] The C20 template was replaced with a poly-T DNA having a base sequence length of 20, denoted as T20, and ZnO-4 and H-ZnO-4 were obtained according to the preparation method of Example 1.

[0075] Example 5

[0076] The C20 template was replaced with a poly-G DNA having a base sequence length of 20, denoted as G20, and ZnO-5 and H-ZnO-5 were obtained according to the preparation method of Example 1.

[0077] Example 6

[0078] The C20 template was replaced with a poly-C DNA having a base sequence length of 30, which was recorded as C30, and ZnO-6 and H-ZnO-6 were obtained according to the preparation method of Example 1.

[0079] Example 7

[0080] The template C20 was replaced with an A / T double-stranded DNA with a base length of 20, denoted as A / T20, and ZnO-7 and H-ZnO-7 were obtained according to the preparation method of Example 1.

[0081] Example 8

[0082] The template C20 was replaced with a C / G double-stranded DNA with a base length of 20, recorded as C / G20, and ZnO-8 and H-ZnO-8 were obtained according to the preparation method of Example 1.

[0083] Example 9

[0084] The template C20 was replaced with free cytosine, recorded as Cytosine, and ZnO-9 and H-ZnO-9 were obtained according to the preparation method of Example 1.

[0085] Comparative Example 1

[0086] Without adding a DNA template, ZnO-10 and H-ZnO-10 were obtained according to the preparation method of Example 1.

[0087] The morphology of ZnO-1 to ZnO-10 was observed using a transmission electron microscope (TEM). Figure 1 As shown in the figure, ZnO-1, ZnO-2 and ZnO-6 present a uniform and stable spindle-shaped structure, while the spindle-shaped structures of ZnO-3 to ZnO-5 and ZnO-7 to ZnO-9 are incomplete, and ZnO-10 is fragmented, disordered and uneven.

[0088] Dynamic light scattering (DLS) was used to analyze ZnO-1~ZnO-10. The results showed that the particle size and PDI of ZnO-1~ZnO-9 were significantly lower than those of ZnO-10. The particle size of ZnO-1 was about 254nm, and the PDI was 0.06. The particle size of ZnO-2 was about 198nm, and the PDI was 0.32. The particle size of ZnO-3~ZnO-9 was also in the range of 205-330nm, and the PDI was between 0.18-0.38. The particle size of ZnO-10 was 360nm, and the PDI was 0.5.

[0089] The results show that adding DNA template to the ZnO nanoparticle synthesis system can significantly reduce the size of the nanoparticles and improve the uniformity, and under preferred conditions, such as the conditions shown in Example 1, ZnO nanoparticles with good morphology can also be obtained.

[0090] Test Example 1: Comparison of the appearance and performance of ZnO-1 and H-ZnO-1 obtained in Example 1 to evaluate the effect of the modification treatment on ZnO nanoparticles

[0091] The TEM morphology results of ZnO-1 and H-ZnO-1 are shown in Figure 2 As shown in the figure, after being treated with H2O2, the morphology of the nanoparticles is similar, still showing a spindle-shaped structure, but the surface roughness is significantly increased, forming a nanostructure similar to that of Xanthium sibiricum.

[0092] Through ICP-OES test analysis, H2O2 treatment has no effect on the Zn content of the nanoparticles. According to the Zn feed amount, the final yield of H-ZnO-1 prepared is as high as 99%.

[0093] like Figure 3 , Figure 4 As shown in the figure, after H2O2 modification, the particle size and PDI of the nanoparticles did not change significantly, while the ζ potential dropped from -23 mV to -28 mV, further indicating that the surface structure of the nanoparticles changed.

[0094] UV-Vis results are as follows Figure 5 As shown, the results show that ZnO-1 has characteristic absorption peaks of DNA and ZnO crystal at 260nm and 360nm respectively; H-ZnO-1 still has absorption at 260nm and 360nm, but there is no obvious absorption peak at 260nm.

[0095] Infrared absorption spectrum Figure 6 As shown in the figure, the infrared absorption spectra of ZnO-1 and H-ZnO-1 are similar, both at 452 cm -1 The stretching vibration peaks of ZnO appear on the left and right, while the remaining absorption peaks mainly come from DNA.

[0096] like Figure 7 Raman spectra show that ZnO-1 and H-ZnO-1 have -1 and 1100cm -1 The characteristic absorption peaks of ZnO appeared on both sides, and H-ZnO-1 was at 830cm -1 A new peak related to ZnO2 appeared.

[0097] Using FAM to label DNA bio-template, fluorescently labeled ZnO-11 and H-ZnO-11 were prepared according to the method of Example 1. DNA was fluorescently labeled with FAM, and fluorescence quantitative analysis confirmed that H2O2 modification treatment would not cause DNA to desorb from the surface of ZnO nanoparticles. EDS elemental analysis results showed that the elemental composition of ZnO-11 was Zn and O, and contained a small amount of P and N, indicating that DNA was adsorbed on the surface of ZnO nanoparticles; and EDS scanning results showed that DNA was distributed on the cross section of ZnO-11. After H2O2 treatment, the Zn / O atomic number ratio in the nanoparticles changed from 1:0.74 to 1:0.86, indicating that the proportion of oxygen increased, indicating that part of the ZnO in the structure may be oxidized to ZnO2 by H2O2, and EDS scanning diagram analysis found that the distribution of N and P on the surface of the nanoparticles increased, indicating that part of the DNA was exposed on the surface of the nanoparticles after H2O2 treatment.

[0098] Test Example 2: Placement Stability Test

[0099] Example 1 Freshly prepared ZnO-1 and H-ZnO-1 are both milky white colloidal solutions with a concentration of 320 μg / mL (in terms of Zn, the same below). The changes before and after leaving them at room temperature for 24 hours are as follows: Figure 8 shown.

[0100] The results showed that after 24 hours, ZnO-1 aggregated and precipitated, but H-ZnO-1 could still maintain a stable dispersion state. When the nanoparticles were dispersed in PBS buffer and cell culture medium, it was also found that ZnO-1 rapidly aggregated in the two physiological matrices, while the particle size of H-ZnO-1 remained stable during the 3-day observation period. The above results show that the modified ZnO nanoparticles have stronger colloidal stability.

[0101] Test Example 3: Acid Stability Test

[0102] The ZnO-1 and H-ZnO-1 prepared in Example 1 were dispersed in sodium acetate buffer (concentration of 10 mM, pH 5.5) and phosphate buffer (concentration of 10 mM, pH 7.4), respectively, and the Zn in the supernatant of different groups was detected by ICP-OES. 2+ content and calculate the release rate, such as Fig. 9 shown.

[0103] The results showed that both ZnO-1 and H-ZnO-1 could remain stable in the buffer solution with pH 7.4, and no ZnO-1 was found within 12 h. 2+ When the pH dropped to 5.5, ZnO-1 rapidly released Zn within 5 min. 2+ And reaches a platform, at this time Zn 2+ The cumulative release rate of ZnO-1 was about 62.5%. In comparison, the release rate of H-ZnO-1 was significantly lower, and it was released slowly within 3 hours, and then reached a plateau. 2+ The cumulative release is about 50%.

[0104] The microscopic morphology of the two nanoparticles after being treated in sodium acetate buffer at pH 5.5 for 5 min and 30 min is shown in Figure 2. Fig.10 As shown in the figure, after 30 minutes of treatment under acidic conditions, the number of ZnO-1 particles decreased significantly, and the particle size also decreased significantly; while H-ZnO-1 can still observe a large number of spindle-shaped nanoparticles with uniform morphology in the field of view, and the particle size change is not obvious. The above results all confirm that the modified ZnO nanoparticles have stronger acid stability, which may be attributed to the change in their surface properties.

[0105] Test Example 4: Photocatalytic activity test

[0106] The quantitative results of color and ultraviolet absorption between TMB (reduced state) and ox-TMB (oxidized state) of ZnO-1 and H-ZnO-1 obtained in Example 1 confirmed that H-ZnO-1 had excellent photocatalytic activity and was concentration-dependent, and had stronger photocatalytic activity than ZnO-1.

[0107] ESR was used to further detect the concentrations of nanoparticles before and after irradiation with 254nm ultraviolet light for 15min. - The signal strength, such as Fig.11 , Fig.12 The results show that at the same concentration, H-ZnO-1 group ·OH and ·O2 - The signals of the modified ZnO nanoparticles were significantly stronger than those of the ZnO-1 group; and as the concentration of H-ZnO-1 increased, the signal peaks of the two active oxygen species increased, which was consistent with the results of the TMB experiment. The results showed that the photocatalytic activity of the modified ZnO nanoparticles was stronger.

[0108] Test Example 5: Antibacterial Activity Test

[0109] The antibacterial activity of ZnO nanoparticles was investigated using two bacteria, Staphylococcus aureus (S. aureus, Gram-positive bacteria) and Escherichia coli (E. coli, Gram-negative bacteria). The results of the agar diffusion experiment showed that H-ZnO-1 had a more obvious inhibition zone than ZnO-1, indicating that H2O2 treatment significantly enhanced the antibacterial activity of ZnO nanoparticles. Compared with H-ZnO-3 to H-ZnO-5 obtained in Examples 3, 4, and 5, H-ZnO-1 obtained in Example 1 had a larger inhibition zone, indicating that it had stronger antibacterial activity, indicating that a more uniform nanosize helps to enhance the antibacterial activity of the modified ZnO nanoparticles.

[0110] The antibacterial activity of the ZnO-1 and H-ZnO-1 obtained in Example 1 against Staphylococcus aureus and Escherichia coli was tested by gradient dilution method under the condition of light or not: the nanoparticles were mixed with the bacteria respectively, and cultured continuously for 12 h in an incubator at 37°C and 180 rpm under light-proof and light-proof conditions, and then the OD of each group was tested. 600 ; Combined plate method was used to detect the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ZnO-1 and H-ZnO-1 against the two bacteria. Fig.13 , Fig.14 As shown in Table 1.

[0111] Table 1 MIC / MBC of ZnO-1 and H-ZnO-1 against bacteria under different illumination conditions

[0112]

[0113] The results showed that the growth inhibition of ZnO-1 on Staphylococcus aureus and Escherichia coli gradually increased with the increase of nanoparticle concentration, but its inhibition was not affected by light, indicating that within this concentration range, the antibacterial activity of ZnO-1 had no obvious correlation with its photocatalytic effect, and it was speculated that it was mainly related to the contact between ZnO-1 and bacteria. Through quantitative analysis, the minimum inhibitory concentration (MIC) / minimum bactericidal concentration (MBC) of ZnO-1 on Staphylococcus aureus and Escherichia coli were 80μg / mL and 320μg / mL respectively.

[0114] The growth inhibition effect of H-ZnO-1 on both bacteria was significantly stronger than that of ZnO-1, and light could further enhance its antibacterial activity, especially when the nanoparticle concentration was 10 μg / mL, its antibacterial activity was significantly enhanced, indicating that within the concentration range, photocatalysis also contributed to the antibacterial activity of H-ZnO-1, which was attributed to the stronger photocatalytic ability of H-ZnO-1. The plate coating experiment showed that when protected from light, the MIC / MBC of H-ZnO-1 against Staphylococcus aureus and Escherichia coli were both 20 / 40 μg / mL; when stimulated by light, the MIC / MBC of H-ZnO-1 against Staphylococcus aureus decreased to 10 / 20 μg / mL, and the MIC / MBC against Escherichia coli decreased to 10 / 40 μg / mL, further confirming the effect of photocatalysis on the antibacterial ability of H-ZnO-1.

[0115] Staphylococcus aureus and Escherichia coli were directly exposed to Zn 2+ Incubation, gradient dilution experiment results showed that Zn 2+ The growth inhibition effect of ZnO-1 on the two bacteria was significantly weaker than that of ZnO-1. The MICs of ZnO-1 and H-ZnO-1 against Staphylococcus aureus and Escherichia coli were 50 μg / mL and 100 μg / mL, respectively, and the MBC was ≥ 200 μg / mL, indicating that the antibacterial activity of ZnO-1 and H-ZnO-1 mainly originated from their nanostructure and properties, rather than the released Zn 2+ .

[0116] Test Example 6: Bacterial Adhesion Test

[0117] Two types of nanoparticles (MIC) labeled with DNA fluorescence, ZnO-11 and H-ZnO-11, were mixed with bacteria respectively and cultured continuously in an incubator at 37°C and 180 rpm for 12 h. The bacteria were recovered by centrifugation at 5000 rpm for 10 min and then washed three times with PBS. The content of nanoparticles adsorbed on the surface of the bacteria was observed and photographed using an inverted fluorescence microscope.

[0118] The results showed that the two nanoparticles adhered significantly more to Escherichia coli than to Staphylococcus aureus. At the same time, the H-ZnO-11-treated group had stronger fluorescence signals in both bacteria, indicating that more H-ZnO-11 adhered to the bacterial surface.

[0119] TEM can be used to more intuitively observe the bacteria treated with nanoparticles, such as Fig.15 As shown. The results showed that the cytoplasm of Staphylococcus aureus in the ZnO-11 treatment group showed obvious aggregation (yellow arrow), but no obvious nanoparticles were observed on the bacterial surface; in the H-ZnO-11 treatment group, a large number of nanoparticles were adhered to the bacterial surface (green arrow), and the bacterial cell wall was obviously damaged and the contents leaked (red arrow). Similar to Staphylococcus aureus, a large amount of H-ZnO-11 was also adhered to the surface of Escherichia coli, and obvious depressions and cell wall damage appeared at the adhesion site, but this phenomenon was not observed in the ZnO-11 treatment group.

[0120] The above experimental results show that the modified ZnO nanoparticles have stronger bacterial adhesion properties, whether it is Staphylococcus aureus or Escherichia coli with an outer membrane on the surface, and stronger bacterial adhesion will help the modified ZnO nanoparticles to exert their antibacterial activity: on the one hand, the modified ZnO nanoparticles adhered to the surface of the bacteria can cause damage to the bacterial cell wall through mechanical extrusion, which is more conducive to the penetration of nanoparticles into the bacteria and further affect the normal life activities of the bacteria through multiple pathways; on the other hand, this close contact also provides a basis for the ROS generated by the nanoparticles after photocatalysis to exert their bactericidal effect.

[0121] Test Example 7: Test of ROS Levels in Bacteria

[0122] To further evaluate the direct destructive effect of ZnO-1 and H-ZnO-1 on bacteria, they were co-incubated with bacteria under light-proof conditions to exclude the influence of photocatalysis, and the effect of nanoparticles on bacterial intracellular homeostasis was investigated using the oxidative stress level as an indicator. The two nanoparticles (MIC) obtained in Example 1 were mixed with bacteria respectively, cultured continuously in a 37°C, 180rpm incubator in the dark for 12h, centrifuged at 5000rpm for 10min to recover the bacteria, washed 3 times with PBS, added DCFH-DA (10μM) and co-incubated in a 37°C bacterial incubator for 30min, observed and photographed using an inverted fluorescence microscope, and the fluorescence intensity was detected using an ELISA reader.

[0123] like Fig.16As shown in the figure, the fluorescence imaging results of the DCFH-DA probe showed that ZnO-1 and H-ZnO-1 treatment could lead to a significant increase in the level of ROS in the bacteria. The statistical results showed that the fluorescence intensity of the H-ZnO-1 group was significantly higher than that of the ZnO group. In addition, the results of optical microscopy showed that the bacteria treated with H-ZnO-1 showed obvious shrinkage and damage, which once again proved the efficient killing effect of H-ZnO-1 on bacteria.

[0124] In order to clarify the effect of ROS on antibacterial effect, ZnO-1 and H-ZnO-1 obtained in Example 1 were co-incubated with bacteria, and N-acetylcysteine ​​(NAC, a strong reducing agent) was added at a final concentration of 5 mM to shield the effect of ROS on bacteria. The results of the gradient dilution experiment showed that the addition of NAC significantly reduced the growth inhibition of nanoparticles on Staphylococcus aureus and Escherichia coli, indicating that the antibacterial effect of ZnO-1 mainly originated from the induction of the production of intracellular ROS in bacteria, and the results showed that after shielding the antibacterial effect of nanoparticles based on ROS, the growth inhibition of H-ZnO-1 on bacteria was still significantly better than that of ZnO-1.

[0125] Test Example 8: Cytotoxicity Test

[0126] Using L929 mouse fibroblasts as a model, 5×10 3 L929 cells were seeded in 96-well plates at 100 μg / well and cultured in a 37°C, 5% CO2 incubator for 24 h. Then, gradient concentrations of ZnO-1 and H-ZnO-1 were added and incubated with the cells for 24 h. Subsequently, the CCK8 method was used to detect and calculate the cell viability of each group. The results are shown in Fig.17 shown.

[0127] The results showed that with the increase of H-ZnO-1 concentration, the cell activity gradually decreased, but within the antibacterial MBC concentration range (S. aureus: 20μg / mL; E. coli: 40μg / mL), the cell survival rate was higher than 80%. The cell killing effect of ZnO-1 was significantly stronger than that of H-ZnO-1. When the concentration reached 40μg / mL, the cell survival rate was less than 50%, indicating that H2O2 treatment can reduce the cytotoxicity of ZnO nanoparticles, thereby improving the biosafety of nanoparticles.

[0128] Test Example 9: Adhesion test of nanoparticles to cells

[0129] The ZnO-1 and H-ZnO-1 obtained in Example 1 were labeled with green fluorescence, and the cytoskeleton was stained (red) with the help of the probe to visually observe the adhesion of nanoparticles to cells. 6CFU / mL Staphylococcus aureus and Escherichia coli were incubated with two nanoparticles (MIC) for 5 minutes, respectively, and then the above mixture was co-incubated with adherent L929 cells at 37°C for 30 minutes, and then the supernatant of each group was collected, centrifuged at 5000rpm for 10 minutes, and then washed 3 times with PBS and then dispersed. The cells were washed 3 times with PBS, and then fixed with 4% paraformaldehyde for 10 minutes, washed with PBS 3 times, permeabilized with 0.5% Triton X-100 for 5 minutes, washed with PBS twice, and incubated with phalloidin cytoskeleton probe (10μM) at 37°C for 30 minutes, and washed with PBS twice. Finally, the mixture of nanoparticles and bacteria was added, and the cells were observed and photographed using an inverted fluorescence microscope. The adhesion of nanoparticles to bacteria and cells when co-incubated with bacteria and cells is shown in the figure. Fig.18 shown.

[0130] The results showed that ZnO-1 had no selectivity for the adhesion of bacteria and cells. In the presence of bacteria, a large amount of ZnO-1 still appeared in the cytoskeleton (white arrows), causing the cytoskeleton to shrink significantly, while only a small amount of H-ZnO-1 appeared in the cells, indicating that the adhesion ability of H-ZnO-1 is bacteria-specific, thereby reducing its toxic side effects on normal cells.

[0131] Test Example 10: Chicken Embryo Chorioallantoic Membrane Test

[0132] The chick embryo chorioallantoic membrane test (HET-CAM) was used to evaluate the vascular irritation of ZnO-1 and H-ZnO-1. Fig.19 The results showed that after 10 minutes of treatment with ZnO-1 and H-ZnO-1, no obvious coagulation and blood vessel rupture occurred, but the blood vessels in the ZnO-1 group showed slight contraction (white arrows), which verified that the modified ZnO nanoparticles had better biocompatibility.

[0133] The results of test examples 1-10 show that the modified ZnO nanoparticles obtained after H2O2 treatment have a rougher surface, their photocatalytic activity and stability are improved, and they also have stronger antibacterial properties and biosafety.

[0134] An external gel was prepared using the ZnO-1 and H-ZnO-1 obtained in Example 1 as raw materials to evaluate the antibacterial effect and healing effect of the nanoparticles on the wound surface.

[0135] Test Example 11: Effects of Nanoparticles on Infected Wounds

[0136] Animals and feeding: SPF-grade healthy ICR male mice (6-8 weeks, 20-24 g) were purchased and fostered by the Experimental Animal Center of Central South University. During the feeding period, the animals had free access to food and water, and were placed in a 12-hour light and 12-hour dark cycle every day. All animal experiments were approved by the Experimental Animal Ethics Committee of Central South University (ethics approval number: XMXH--2023-1229).

[0137] Construction of the wound model of Staphylococcus aureus infection in mice: After the mice were anesthetized, a circular full-cut wound with a diameter of 1 cm was constructed on their backs, and then 100 μL of Staphylococcus aureus suspension (1×10 6 CFU / mL), and the infection lasted for 24 hours. After bacterial infection, the wound showed obvious suppuration and the healing speed slowed down significantly, indicating the successful construction of the infected wound.

[0138] Gel preparation: ZnO-1 and H-ZnO-1 (concentration of 40 μg / mL) prepared in Example 1 were mixed with 3% Carbopol 941 gel at a volume ratio of 1:1 to obtain Carbopol gels containing 20 μg / mL ZnO-1 and H-ZnO-1, respectively. 3% Carbopol 941 gel and double distilled water were prepared at a volume ratio of 1:1 to obtain a blank gel as a control.

[0139] Experimental arrangement: The mice were randomly divided into the following 5 groups (n=6): Normal group, Infected group, Blank gel group, ZnO gel group and H-ZnO gel group. The mice in Normal group were uninfected normal wound group and did not receive any treatment. The other four groups were infected wound groups. The Infected group did not receive any treatment. The Blank gel group was treated with blank carbopol gel, the ZnO gel group was treated with carbopol gel loaded with ZnO-1, and the H-ZnO gel group was treated with carbopol gel loaded with H-ZnO-1. The drugs were administered (100 μL gel / time) on the 1st day (D1), the 3rd day (D3), the 5th day (D5), and the 7th day (D7), respectively.

[0140] On days 1, 3, 5, 7, 9, and 13, photographs were taken to record the wound conditions of the mice. Fig. 20 The results showed that both blank gel (Blank gel group) and ZnO-1 gel (ZnO gel group) could not promote wound healing, and obvious wound marks and scabs could still be observed on the 13th day; while H-ZnO-1 gel (H-ZnO gel group) significantly promoted wound healing, and the wound scabs completely fell off on the 13th day, and its healing rate was not significantly different from that of normal wounds.

[0141] The relative wound area was calculated by ImageJ, and the statistical results are shown in Fig.21 The results showed that the healing rate of the H-ZnO-1 gel group (H-ZnO gel group) and the normal wound group (Normal group) reached 50% on the 7th day, while the other three groups required more than 9 days to heal 50%.

[0142] On the 3rd, 7th and 13th days, mucus from the mouse wounds was smeared on plates and photographed after culturing at 37°C for 24 hours. Fig. 22 Compared with the infected group, the bacterial load in the wound was significantly reduced on the third day after treatment with H-ZnO-1 gel, and almost no bacteria were detected in the wound on the seventh day after two treatments; although the ZnO-1 gel treatment inhibited the growth of wound bacteria to a certain extent, it could not completely kill the wound bacteria.

[0143] H&E staining of the wound skin tissue of mice was performed 13 days after treatment. Fig.23 As shown. The results showed that the wound skin of the infected group (Infected group) was not completely epithelialized and not completely closed, and obvious scabs and a large number of inflammatory cell infiltrations were observed; the wound skin treated with blank gel and ZnO-1 gel had no significant improvement, while the wound epithelialized in the H-ZnO-1 gel was complete and the wound was completely closed. Moreover, the healing effect of the infected wound treated with H-ZnO-1 gel was better than that of the normal wound control group (Normal group), with thicker granulation tissue and no obvious scabs, indicating that the preparation has the ability to promote wound healing.

[0144] After the infected wounds were treated with different preparations for 9 days, the skin around the wounds was taken to prepare tissue homogenates, and the expression levels of cytokines were detected by ELISA, such as Fig.24 The results showed that the expression levels of pro-inflammatory factors, including TNF-α, IL-1β and IL-6, increased significantly after bacterial infection, while the expression of anti-inflammatory factor IL-10 decreased significantly. ZnO-1 gel treatment had no obvious inflammatory regulation effect, but it could effectively reduce the level of pro-inflammatory factors and promote the expression of IL-10.

[0145] After the infected wounds were treated with different preparations for 13 days, α-SMA (red) and CD31 (green) were used to mark the new blood vessels in the proliferative wound tissue. The immunofluorescence staining results are shown in Figure 2. Fig.25 The results showed that H-ZnO-1 gel treatment can significantly promote the formation of blood vessels in wound tissue, while ZnO-1 gel treatment has no obvious effect on promoting blood vessels.

[0146] After the infected wounds were treated with different preparations for 13 days, the skin tissue around the wounds was taken for Masson staining. Fig.26The results showed that after wound infection, the collagen (blue) in the skin decreased and there were more muscle fibers (red) distributed. After treatment with H-ZnO-1 gel, a large amount of collagen was deposited in the wound tissue and arranged in an orderly manner. Although the treatment with ZnO-1 gel increased the deposition of collagen in the infected wound, the arrangement was disordered.

[0147] The above results show that the topical gel made of modified ZnO nanoparticles has a bactericidal effect when applied to infected wounds, can promote wound healing, and can effectively inhibit the outbreak of inflammation in the wound area, promote the transition of the wound from the inflammatory stage to the proliferative stage, accelerate the remodeling of the wound, and reduce the formation of scars.

[0148] Test Example 12: Effects of Nanoparticles on Non-Infected Wounds

[0149] The method of Test Example 11 was followed, except that the wound was not infected with bacteria. The wounds were divided into Control group, Blankgel group, ZnO gel group and H-ZnO gel group. The Control group was a control group and no treatment was done on the wound.

[0150] The wound conditions of the mice were recorded on days 1, 3, 5, 7, 9, and 13, and the relative wound area was calculated using ImageJ. The results are shown in the figure. Fig. 27 , Fig.28 The results showed that the treatment with ZnO-1 gel significantly delayed the healing speed of the wound, and the healing effect of H-ZnO-1 gel was significantly better than that of ZnO-1 gel, and the wound was closed on the 13th day after treatment. Among the various treatment groups, the wounds in the H-ZnO-1 gel group (H-ZnO gel group) had less scabs and better healing status.

[0151] After 9 days of treatment with different preparations, the skin around the wound was taken to prepare tissue homogenate, and the cytokine expression levels were detected by ELISA, such as Fig.29 The results showed that blank gel and ZnO-1 gel treatment increased the expression of pro-inflammatory factors in skin tissue, indicating that it prolonged the inflammatory phase of normal wound healing, while there was no significant difference between the H-ZnO-1 gel group (H-ZnO gel group) and the normal group (Control group).

[0152] On the 13th day, the skin around the wound of mice was taken for immunofluorescence staining with α-SMA (red) and CD31 (green) to mark the new blood vessels in the proliferative wound tissue. The results of immunofluorescence staining are shown in Fig.30 The results showed that the number of new blood vessels in the wound was reduced after treatment with ZnO-1 gel, while a large number of new blood vessels could be observed in the wound tissue of mice after treatment with H-ZnO-1 gel.

[0153] After 13 days of treatment with different preparations, skin tissues around the wound were obtained and the wound remodeling effect was evaluated by Masson staining, e.g. Fig.31 The results showed that there was more collagen (blue) deposited in an orderly manner at the wound site of mice in the H-ZnO-1 gel group (H-ZnO gel group), but the collagen distribution at the wound site of the blank gel group (Blank gel group) and the ZnO-1 gel group (ZnO gel group) was disorderly.

[0154] Transforming growth factor β (TGF-β) is a growth factor closely related to wound healing. It participates in multiple processes such as inflammatory response, cell proliferation and differentiation, and scar formation. It can induce fibroblasts to differentiate into myofibroblasts and secrete α-SMA, which is one of the important pathological changes in the process of hypertrophic scar formation. To this end, the applicant further detected the expression level of TGF-β in the wound tissue of each group of mice after 13 days of treatment. Fig.32 The results showed that the blank gel group (Blank gel group) and the ZnO-1 gel group (ZnO gel group) significantly increased the expression of TGF-β in wound tissue. Compared with the normal group (Control group), there was no significant difference in the H-ZnO-1 gel group (H-ZnO gel group) after treatment, indicating that it is expected to avoid scar formation.

[0155] The above results show that although the application of topical gel containing modified ZnO nanoparticles on ordinary wound surfaces cannot significantly increase the healing speed of wounds, it can effectively improve the repair of wounds during the remodeling period and promote scar-free healing of wounds.

[0156] During the test examples 11 and 12 experiments, the weight of mice was recorded and analyzed every 2 days. The results showed that there was no significant difference in the weight of mice in each group, indicating that the application of ZnO-1 gel and H-ZnO-1 gel on the wound surface would not produce obvious systemic toxicity. Mice were killed on the 9th and 13th days respectively, and the liver and kidney indicators (ALT, AST, BUN, Cre) of mice were detected by eye blood sampling. The results showed that after bacterial infection, the liver and kidney indicators of mice were abnormal, but after treatment with H-ZnO-1 gel, each indicator was restored to normal levels. After the treatment was completed, H&E staining was used to analyze the pathological changes of the main organs of each group of mice. The results showed that there were no obvious pathological changes in all the main organs of all mice, indicating that the external gel prepared by using the modified ZnO nanoparticles obtained by the present invention as raw materials was safe for wound treatment and would not produce obvious toxic and side effects.

[0157] The present invention first synthesizes spindle-shaped ZnO nanoparticles with uniform morphology using DNA as a template, and then further treats the ZnO nanoparticles with H2O2 to obtain modified ZnO nanoparticles. Experimental results show that H2O2 treatment significantly increases the roughness of the surface of ZnO nanoparticles, slows down their degradation rate in an acidic environment, and enhances their photocatalytic activity. This modified ZnO nanoparticle with a "Xanthium sibiricum"-like morphology and special properties has the following unique advantages in in vivo anti-infection wound healing: First, its rough surface effectively enhances the adhesion of nanoparticles to bacteria: on the one hand, the physical extrusion between nanoparticles and bacteria can enhance the sensitivity of bacteria to external stimuli by damaging the cell wall; on the other hand, this close adsorption helps to enhance the close-range killing of bacteria by ROS generated by the photocatalysis of modified ZnO nanoparticles, significantly improving the antibacterial activity; secondly, the modified ZnO nanoparticles can slowly release Zn under acidic conditions. 2+ , avoiding high concentrations of Zn 2+ potential safety issues; finally, the modified ZnO nanoparticles slowly release Zn at the wound site 2+ , which helps to quickly repair wounds during the remodeling period. Experiments have shown that after the wound is treated with modified ZnO nanoparticles, the bacteria in the wound area can be quickly cleared, thereby accelerating the healing and repair of infected wounds. Moreover, modified ZnO nanoparticles can play a good therapeutic role in different types of wounds.

[0158] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing modified ZnO nanoparticles, characterized in that: ZnO nanoparticles were prepared using Zn salt as raw material and DNA as template, and then treated with H2O2 solution to obtain modified ZnO nanoparticles.

2. The method for preparing modified ZnO nanoparticles according to claim 1, characterized in that: The Zn salt is ZnCl2, ZnSO4, Zn(OAc)2, Zn(NO3)2, ZnCO3, Zn3(PO4)2, ZnBr2, Zn(C6H 11 O7)2 at least one.

3. The method for preparing modified ZnO nanoparticles according to claim 1, characterized in that: The concentration of the DNA is 0.0001-100 μM.

4. The method for preparing modified ZnO nanoparticles according to claim 1, characterized in that: The DNA is single-stranded DNA.

5. The method for preparing modified ZnO nanoparticles according to claim 4, characterized in that: The single-stranded DNA is one of poly-A DNA, poly-T DNA, poly-C DNA and poly-G DNA.

6. The method for preparing modified ZnO nanoparticles according to claim 4, characterized in that: The base length of the single-stranded DNA is 1-40 bases.

7. The method for preparing modified ZnO nanoparticles according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing Zn(OAc)2 and poly-C DNA with a base sequence length of 20 bases in water, heating the mixture, adjusting the pH to alkaline, and obtaining a reaction solution containing ZnO nanoparticles; adding a 30% H2O2 solution to the reaction solution, mixing the mixture, heating the mixture, filtering and washing the mixture, and obtaining modified ZnO nanoparticles.

8. An application of modified ZnO nanoparticles obtained by the preparation method according to claim 7, characterized in that: The invention comprises taking the modified ZnO nanoparticles as raw materials to prepare an external preparation.

9. The use according to claim 8, characterized in that The external preparation is used for wound surface antibacterial.

10. The use according to claim 8, characterized in that The external preparation is used to promote wound healing.